OPTIMIZATION OF THE ROLE OF ASSET RECOVERY CENTER (PPA) OF THE ATTORNEY-GENERAL’S OFFICE OF THE REPUBLIC OF INDONESIA IN ASSET RECOVERY OF CORRUPTION CRIME RESULTS - Suud, Aghia Khumaesi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
The Asset Recovery Center (PPA) as the Republic of Indonesia General Attorney's unit is responsible for ensuring that asset recovery in Indonesia is conducted with an integrated system that is effective, efficient, transparent and accountable, by tracing, securing, maintaining, seizing, and returning assets of criminal acts of corruption handled by the Prosecutor's Office. However, the number of asset recovery resulting from corruption by the PPA remains small, and the current implementation is only done after a court decision, even though asset tracking should be done before the verdict. In addition, the urgency of its existence remains questionable given its scope is almost equal to the Labuksi KPK and Rupbasan at the Ministry of Law and Human Rights, which indirectly creates a tug of war between the law enforcement units. Therefore, using a normative juridical approach and data obtained directly through library research and interview mechanisms, this paper found the importance of establishing a PPA for the Prosecutor's Office related to its duties and functios, as described in the Law and other regulations in the recovery of assets resulting from corruption, which does have a different position from the Labuksi KPK and Rupbasan. This paper also discusses the steps that must be taken by the Prosecutor's PPA to optimize the work of the Prosecutor's PPA so that assets resulting from corruption can be recovered quickly, effectively and transparently.